2019
DOI: 10.1242/jeb.202853
|View full text |Cite
|
Sign up to set email alerts
|

Changes in vitellogenin expression caused by nematodal and fungal infections in insects

Abstract: This study examined the expression and role of vitellogenin (Vg) in the body of the firebug Pyrrhocoris apterus (Heteroptera, Insecta) during infection elicited by two entomopathogenic organisms, the nematode Steinernema carpocapsae and the fungus Isaria fumosorosea. Infection by S. carpocapsae significantly upregulated Vg mRNA expression in the male body. The corresponding increase in Vg protein expression was also confirmed by electrophoretic and immunoblotting analyses. Remarkably, in females, the opposite … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 52 publications
0
11
0
Order By: Relevance
“…Vg is synthesized in the fat body and accumulates in hemolymph, and its levels are negatively impacted by brood rearing and even by exposure to brood pheromone alone 30 . In addition to its role as a precursor of yolk protein in reproduction, Vg has also been implicated in the defense against reactive oxygen species [37][38][39] and as an enhancer of innate immunity 40 .…”
Section: Discussionmentioning
confidence: 99%
“…Vg is synthesized in the fat body and accumulates in hemolymph, and its levels are negatively impacted by brood rearing and even by exposure to brood pheromone alone 30 . In addition to its role as a precursor of yolk protein in reproduction, Vg has also been implicated in the defense against reactive oxygen species [37][38][39] and as an enhancer of innate immunity 40 .…”
Section: Discussionmentioning
confidence: 99%
“…Vitellogenin is another important insect protein, which is considered to provide nutrients for the development of yolk (Antúnez et al, 2013 ; Kodrík et al, 2019 ; Yang, 2020 ). However, many studies have shown that vitellogenins play important roles in the immune systems of amphioxus, potato psyllid, honeybees, Aedes aegypti , and so on (Raikhel et al, 2002 ; Antúnez et al, 2013 ; Shen et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Vitellogenins are actively involved in defence reactions against various pathogens [9]. There was a significant reduction in both ~100 kDa vitellogenin proteins by 8.2-fold and 2.9-fold in the female haemolymph 6 h after venom administration (Figure 8A,B).…”
Section: Effect Of Venom and Akh On Selected Metabolitesmentioning
confidence: 96%
“…The recent identification of vitellogenin in bee venom [7] suggests that it increases the allergenic properties of the venom; however, this has not been studied in detail. Vitellogenins are mostly known as yolk precursors involved in reproduction, but they also play important roles in protection against oxidative stress, wound healing, and insect immunity, with strong activity against bacteria and other pathogens [8,9].…”
Section: Introductionmentioning
confidence: 99%